"СКРЫТЫЕ" СОЛНЕЧНЫЕ ЦИКЛЫ – АНАЛИЗ РАЗВИТИЯ 23-ГО ЦИКЛА КАК РЕЗУЛЬТАТ ПРОЯВЛЕНИЯ АКТИВНОСТИ СЕВЕРНОГО И ЮЖНОГО ПОЛУШАРИЯ СОЛНЦА - Рябов, М. И.; Сухарев, А. Л.; Лукашук, С. А. (Одеські астрономічні публікації, 2011)
Comparison of the basic properties of 23rd cycle of activity on all solar disk and on northern and to southern hemisphere separately is held. As the basic indicators of development of a cycle the data of daily and monthly average data of sunspots numbers – W and the areas of sunspots groups – Sp, flaire index – FI were used. It is shown that duration of the basic phases of a cycle appears different for northern and southern hemispheres. Thus integrated indicators of indexes on all solar disk are only superposition of real physical processes occurring in northern and southern hemispheres. At the same time incidental "synchronisation" of activity of both hemispheres of the Sun is marked. With application of a method correlation, periodogramm and weivlet the analysis the cores «spectra of the periods» changes of indexes and their evolution throughout all cycle of activity are defined. «Spectra of the periods» are formed by occurrence on a disk of complexes of active areas (CAR) and activity complexes (CА) well distinguishable on maps of millimeter emission of the Sun.